Enantioselective Synthesis of 1- and 4-Hydroxytetrahydrocarbazoles through Asymmetric Transfer Hydrogenation - Dilek, Ömer; Patir, Süleyman; Ertürk, Erkan (Synlett, 2019)
Several 1- and 4-hydroxytetrahydrocarbazoles were prepared in high yields (up to 99%) and excellent enantiomeric excesses (up to >99% ee) from the corresponding 1- and 4-oxotetrahydrocarbazoles through asymmetric transfer hydrogenation by using the commercially available Noyori–Ikariya ruthenium catalyst. The immediate use of the freshly prepared catalyst and the use of a HCO2H–DABCO (11:6) mixture as the hydrogen source are crucial for achieving high activity and enantioselectivity. In this way, a tetrahydrocarbazole heterocycle fused to a lactone moiety was synthesized in 45% yield and 97% ee.
Keywords: asymmetric synthesis; transfer hydrogenation; tetrahydrocarbazolones; hydroxytetrahydrocarbazoles; hexahydrofurocarbazolone; ruthenium catalysis